(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The aim of this study was to evaluate the efficacy of inclusion of the fractured vertebra in short segment fixation in terms of clinical and the radiological outcomes in unstable thoracolumbar junction burst fractures at a minimum of 1 year follow-up. Records of 52 patients (age: 21-50 years) with thoracolumbar burst fracture (T10L2) in Magerl Type A fractures underwent posterior pedicle screw fixation including the fractured vertebra. Clinical parameters were back pain using Visual Analogue Score (VAS) and disability using Oswestry disability index (ODI), neurological deficit (using ASIA grade) and radiologic parameters (Cobb angle, the kyphotic deformation and vertebral height) were measured before surgery and at 3, 6 and 12 months post-operatively. The presence of screw breakage, screw pullout, peri-implant loosening, and rod breakage were considered as criteria for implant failure. The majority of fractures resulted due to falls (31 cases), and the remaining cases resulted from car accidents (21 cases). The fractured vertebral body level was L1, T12, L2, T11, and T10 in 23, 17, 6, 4 and 2 cases and achieved satisfactory clinical outcomes according to the modified Mcnab criteria 18, 25, 6 and 3 cases were considered to have excellent, good, fair, and poor outcome. The mean kyphotic angle at pre-, post-operative and final follow-up was 13.5 ± 6.3, 13.4 ± 4.3, 8.5 ± 6. The average loss of kyphosis correction was 6.4 ± 5.2° at the final follow-up. The mean pre- and post-operative kyphotic deformation of vertebral body was 5.1 ± 3.2, 4.8 ± 2.3 and at final follow-up was 4.5 ± 4.0 (p>0.05). The mean anterior and posterior vertebral height also showed significant improvements post-operatively, which were maintained at the final follow-up. The mean ODI and VAS scores at the end of 1 year were 17.4%, 1.7 respectively. There was no case of major complication after surgery and during the follow-up period. In conclusion, reduction of unstable thoracolumbar junction burst fracture can be achieved and maintained with the use of short-segment pedicle screw fixation including the fractured vertebra, avoiding the need for anterior reconstruction.